2021
DOI: 10.1080/01443615.2020.1867965
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of surgical intervention in patients with tubo-ovarian abscess

Abstract: Background: The prediction of antibiotic treatment failure is helpful to identify patients with a high likelihood of needing surgical treatment early in patients diagnosed with tubo-ovarian abscess (TOA). The aim of this study was to compare the clinical characteristics of patients with TOA) who responded to medical treatment and those who underwent surgical intervention due to medical treatment failure. Material and Methods: Electronic medical records were evaluated retrospectively to identify patients who we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Recommendations for drainage may be strengthened in cases of leukocytosis as our logistic regression modeling noted the independent association of increasing white blood cell count with failure of primary medical management. This nding is supported by three previous studies noting a similar association, citing a threshold of 15x10 3 /uL across all studies [12,[15][16][17].…”
Section: Discussionsupporting
confidence: 84%
“…Recommendations for drainage may be strengthened in cases of leukocytosis as our logistic regression modeling noted the independent association of increasing white blood cell count with failure of primary medical management. This nding is supported by three previous studies noting a similar association, citing a threshold of 15x10 3 /uL across all studies [12,[15][16][17].…”
Section: Discussionsupporting
confidence: 84%
“…Fouks et al also found no added value for mean CRP values at admission, even after multivariate analysis (15). Hwang et al reported that although WBC, CRP, and ESR levels were statistically significantly higher in the surgical intervention group than in the conservative treatment group in the univariate analysis, only ESR was significant in multivariate analysis (23). Similarly, in our study, the mean CRP level in univariate analysis was significantly higher in the surgical intervention group (205±109 mg/L) than in the conservative treatment group (115±90 mg/L).…”
Section: Discussionmentioning
confidence: 98%
“…Presenting symptoms and signs of patients One patient was excluded because she was a virginwas observed between treatment type and NLR in the correlation analysis(25). Hwang et al found that NLR had only borderline significance in the univariate analysis(23).Levin et al …”
mentioning
confidence: 99%
“…4,6,7,9,10,17,21,22,29,31 The reported cutoff values of abscess size for surgical therapy need varied between the 5 and 7.4 cm with the sensitivity of 60.5%-89% and the specificity of 50%-92%. 7,8,10,11,[16][17][18][21][22][23][26][27][28]31,32 In all studies included in the meta-analysis, the mean abscess size was larger than 5.9 cm in the surgical therapy groups. In the light of these knowledge, it could be considered that the surgical therapy need is higher in women older than 40 years of age and with the abscess size larger than 6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Study characteristics presented in Table 1 were extracted by four authors independently 4–32 . The fifth author reviewed the extracted data.…”
Section: Methodsmentioning
confidence: 99%